Predisposing Factors Associated with Dengue Prevention Behavior in Pagelaran Health Center Lampung 2025 - Yanti, Dhini Easter; Dwi Nuryani, Dina; Sary, Lolita; Anggeriani, Jheni (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Dengue hemorrhagic fever (DHF) is a serious and potentially fatal disease caused by the dengue virus, transmitted through the bite of the Aedes aegypti mosquito. Objectives: The purpose of this study was to determine the relationship between predisposing factors and dengue fever prevention behavior in the Pagelaran Health Center work area in 2025. Methods: This type of research is quantitative with a cross-sectional approach. The study population consisted of the community residing in and covered by the Pagelaran Health Center work area, with a sample size of 100 respondents selected using proportional stratified random sampling techniques. Data were collected using a questionnaire as a tool. Results : The study showed that most people in the Pagelaran Health Center work area had limited knowledge (81%), negative attitudes (90%), negative perceptions (88%), and poor dengue prevention behaviors (89%). The results indicated a relationship between knowledge and dengue prevention behavior (p-value = 0.032; OR = 4.464), attitudes and dengue prevention behavior (p-value = 0.012; OR = 7.905), and perceptions and dengue prevention behavior (p-value = 0.025; OR = 5.786). Conclusion: These findings imply the need to strengthen health promotion through regular socialization and education, the application of persuasive communication, and active community involvement in dengue fever prevention activities.